Effects of climate change and management on net climate impacts of production and utilization of energy biomass in Norway spruce with stable age-class distribution - Torssonen, Piritta; Kilpeläinen, Antti; Strandman, Harri; Kellomäki, Seppo; Jylhä, Kirsti; Asikainen, Antti; Peltola, Heli (Wiley-Blackwell, 2016)
We studied the effects of climate change and forest management scenarios on net climate impacts (radiative forcing) of production and utilization of energy biomass, in a Norway spruce forest area over an 80-year simulation period in Finnish boreal conditions. A stable age-class distribution was used in model-based analyses to identify purely the management effects under the current and changing climate (SRES B1 and A2 scenarios). The radiative forcing was calculated based on an integrated use of forest ecosystem model simulations and a life cycle assessment (LCA) tool. In this work, forest-based energy was used to substitute coal, and current forest management (baseline management) was used as a reference management. In alternative management scenarios, the stocking was maintained 20% higher in thinning compared to the baseline management, and nitrogen fertilization was applied. Intensity of energy biomass harvest (e.g. logging residues, coarse roots and stumps) was varied in the final felling of the stands at the age of 80years. Also, the economic profitability (NPV, 3% interest rate) of integrated production of timber and energy biomass was calculated for each management scenario. Our results showed that compared to the baseline management, climate benefits could be increased by maintaining higher stocking in thinning over rotation, using nitrogen fertilization and harvesting logging residues, stumps and coarse roots in the final felling. Under the gradually changing climate (in both SRES B1 and A2), the climate benefits were lower compared to the current climate. Trade-offs between NPV and net climate impacts also existed.
Keywords: climate change; climate impact; energy biomass; forest management; radiative forcing; substitution; forest bioenergy production; carbon-dioxide emissions; life-cycle assessment; residues; sequestration; neutrality; stands; timber; fuels; debt